Structure-guided design of antibacterials that allosterically inhibit DNA gyrase. Issue 11 (1st June 2019) - Thalji, Reema K.; Raha, Kaushik; Andreotti, Daniele; Checchia, Anna; Cui, Haifeng; Meneghelli, Giovanni; Profeta, Roberto; Tonelli, Federica; Tommasi, Simona; Bakshi, Tania; Donovan, Brian T.; Howells, Alison; et al.
Graphical abstract: Abstract: A series of DNA gyrase inhibitors were designed based on the X-ray structure of a parent thiophene scaffold with the objective to improve biochemical and whole-cell antibacterial activity, while reducing cardiac ion channel activity. The binding mode and overall design hypothesis of one series was confirmed with a co-crystal structure with DNA gyrase. Although some analogs retained both biochemical activity and whole-cell antibacterial activity, we were unable to significantly improve the activity of the series and analogs retained activity against the cardiac ion channels, therefore we stopped optimization efforts.